Pemegang Polis Asuransi Dan Kedudukan Hukumnya - Sunarmi ' (Jurnal Ilmu Hukum, 2012)
Insurance plays an important role, because in addition to providing protection against the possibilities of losses that will happen, insurance gives a huge boost to the development of other economies. Unfortunately in practice guarantees legal protection of insurance policyholders are less protected. The problems experienced by the policyholder is always the difficulty of obtaining payment of compensation when evenement happen. The reason why the policy is not paid by insurance companies is due to a lack of knowledge of the community itself, but also because of the insurance agent.